PENGARUH KEPEMIMPINAN, REWARD, DAN PUNISHMENT TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. INDAL STEEL PIPE - Kusuma Nara Wicaksana, Loftyan; Ainul Hidayati, Roziana; Cahyadi, Nur (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study aims to determine the influence of leadership, reward and punishment on employee work discipline at PT. Indal Steel Pipe. This study is study with a quantitative approach. The location of this research is PT. Indal Steel Pipe, the variables in this research are leadership, reward, punishment. The population in this study were employees of PT. Indal Steel Pipe. The sample in this research was 102 employees of PT. Indal Steel Pipe. The sampling technique is nonprobability sampling technique or saturated sampling technique. The data collection technique used was by distributing questionnaires. The analysis tool used is SmartPLS 3.0. Based on the results of the research, it was found that leadership, reward and punishment had a positive and significant effect on employee work discipline at PT. Indal Steel Pipe.